THE EFFECTIVENESS OF ERROR MONITORING STRATEGY TO OVERCOME ERRORS IN A RECOUNT TEXT WRITTEN BY TENTH GRADERS (RETAIN, 2015)
Abstract Based on 2013 curriculum, the tenth graders are expected to write a recount text. In writing a recount text the students should be aware of using correct grammatical patterns so as to avoid errors. Sometimes students make some errors because they do not understand well about grammar. Based on that case, Error Monitoring Strategy are needed to help the students in reducing error in writing recount text. This research had three purposes; the first, to find out the kind of errors which are monitored by using error monitoring strategy. The second, to find out the significant difference in number of errors in recount text written by tenth graders before and after using monitoring strategy. The third, to find out the factors which contributing to the reduction of error after using error monitoring strategy.This study used experimental research one group pre test post test design. Data analysis technique used paired t-test on SPSS. The result for the first purpose was the students made 4 types of errors such as omission, addition, misformation and misordering. The result of the second purpose is Sig. = .000 with t = 9.216. The mean in pre-test was 18.55 (SD=10.058) and the mean in post-test was 5.61 (SD=4.835). The mean between pre-test and post-test was 12.947. The result of the third purpose was the strategy itself, listening to music, watching movie with English subtitle, and playing game online as the factor in reducing error. Key words : Writing Skill, Recount Text, Error Monitoring Strategy Abstrak Berdasarkan kurikulum 2013, siswa kelas sepuluh diharapkan untuk menulis teks recount. Saat menulis teks recount siswa harus mengetahui pola tata bahasa untuk menghindari kesalahan menulis. Siswa tidak dapat belajar bahasa tanpa melakukan kesalahan. Terkadang siswa membuat kesalahan karena mereka tidak mengatahui tata bahasa dengan baik. Siswa butuh strategi untuk membatu mereka dalam mengurangi kesalahan dalam tulisan mereka.. Maka dari itu, error monitoring strategy dibutuhkan untuk membantu siswa dalam mengurangi kesalahan dalam menulis teks recount.Penelitian ini mempunyai tiga tujuan, tujuan pertama untuk mengetahui kesalahan apa saja yang dipantau dengan menggunakan error monitoring strategy. Hasilnya adalah siswa membuat 4 macam kesalahan seperti omission, addition, misformation dan misordering. Tujuan kedua adalah untuk mengetahui perbedaan jumlah kesalahan yang signifikan pada sebelum dan sesudah pelaksanaan strategi. Tujuan ketiga adalah untuk mengetahui faktor-faktor apa saja yang dapat mengurangi kesalahan setelah menggunakan error monitoring strategy. Penelitian ini menggunakan eksperimental satu grup pre-test dan post-test design. . Data analisis penggunakan paired sample t-test. Hasil dari tujuan pertama adalah siswa membuat 4 macam error seperti omission, addition, misformation and misordering. Hasil tujuan kedua adalah Nilai rata-rata kesalahan pada pre-test adalah 18.55 (SD=10.058) dan nilai rata-rata kesalahan pada post-test adalah 5.61 (SD=4.835). Nilai rerata jumlah kesalahan antara pre-test dan post-test adalah 12.947. Hasil tujuan ketiga adalah strategi itu sendiri, mendengarkan musik, melihat film dengan teks bahasa Inggris, dan bermain permainan online adalah faktor yang dapat mengurangi error. Kata Kunci : kemampuan menulis, teks recount, error monitoring strategy